Volume 2: Fuels; Numerical Simulation; Engine Design, Lubrication, and Applications 2013
DOI: 10.1115/icef2013-19165
|View full text |Cite
|
Sign up to set email alerts
|

Tailor Made Biofuels: Effect of Fuel Properties on the Soot Microstructure and Consequences on Particle Filter Regeneration

Abstract: In recent years a lot of effort has been made to understand the phenomena of Diesel Particulate Filter (DPF) regeneration processes but less attention has been paid to understand the influence of fuel properties on soot reactivity and its consequence on the DPF regeneration behavior. Within the Cluster of Excellence “Tailor-Made Fuels from Biomass (TMFB)” at RWTH Aachen University, the Institute for Combustion Engines carried out a detailed investigation program to explore the potential of futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…It is very apparent from the curves that all the soot samples possess two significant characteristics peaks. The first peak at ~ 2theta = 23° corresponds to 002 planes and the second peak at ~ 2theta = 44° corresponds mainly to the 100 plane (21) . The main results derived from XRD analysis are summarized in Table 3.…”
Section: Methodology and Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…It is very apparent from the curves that all the soot samples possess two significant characteristics peaks. The first peak at ~ 2theta = 23° corresponds to 002 planes and the second peak at ~ 2theta = 44° corresponds mainly to the 100 plane (21) . The main results derived from XRD analysis are summarized in Table 3.…”
Section: Methodology and Approachmentioning
confidence: 99%
“…On the other hand, the benefits in PM emissions with HVO are mainly attributed to its aromatic free composition as well as its lower distillation range as compared to the petroleum diesel (14) . Previous studies have reported significant variations in the structure and oxidative reactivity of the soot derived from different petroleum based diesel fuels and biofuels (11)(12)(13)(17)(18)(19)(20)(21)(22)(23) . Mikkonen et.…”
Section: Impact Of Biofuels On Particulate Matter and Dpf Behavior-a mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on opacity measurement of the engine exhaust with the photoacoustic device by modulated laser at 808 nm downstream DOC, the exhaust-related extinction coefficient (k ext ) was calculated by Lambert-Beer's law. In order to focus on the soot properties, the influence of un-burnt fuel and oil was reduced by calculating the light absorbing soot amount based on the measured NSOF of the soot 43,44 k ext = ln…”
Section: Optical Propertiesmentioning
confidence: 99%
“…[47][48][49][50] In case of 2-MTHF/DBE, its higher soot reduction potential could be attributed to three main favorable properties such as (1) absence of aromatics, (2) improved local air-fuel ratio due to higher oxygen content and favorable functionality of oxygen atom within the fuel molecular structure, and (3) the enhanced mixing due to high volatility and longer ignition delay. 1,44,47 Soot oxidation kinetics in DPF Figure 10 depicts the magnified view of the Arrhenius plots of all the investigated fuels with soot-O 2 reaction. The results indicate that the activation energy of 2-MTHF/DBE soot oxidation for soot-O 2 reaction decreases ;9 kJ/mol as compared to EN 590 diesel soot.…”
Section: Pm Mass and Number Emissionmentioning
confidence: 99%